(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Higher education sector in Oman has grown and madesignificant development in the last decade. There is heavy investment toimprove the education infrastructure, provide increased education opportunitieswith focus on women education to ensure equality and equity. The spread ofHigher Education Institutions (HEIs) of all types, diversified programmes andestablishment of Quality Assurance Council is a testimony to the importancegiven by the nation to ensure quality of higher education that theneeds/requirements of 21st century are met. In order to achieve aninternational standard in higher education, all HEIs have adopted - importedcurriculum, recruited international / expatriate faculty and English as amedium of instruction. Despite these efforts, the quality of education in termof 21st century, requirement both in terms of knowledge acquisition and skillsseems to be missing and is not up to the desired level. This paper will discuss the role of quality assuranceunits in Higher Education Institutes. The discussion will include anintroduction on the need for Quality Assurance units followed by challengesfacing quality assurance units. The paper then describes the outcomes of an initial needsanalysis that led to the development of a National Quality Plan. Some of thestrategies in this plan for improving and increasing capability are considered,most particularly the establishment of a practitioner‐oriented Oman Quality Network, and the design andimplementation of a National Quality Training Program. These two strategiesattempt to address common obstacles to capability, namely a paradigm thatentrenches compliance and helplessness, and only early awareness of effectivequality enhancement and quality assurance principles and methods.